Effects of boxing-specific training on physical fitness and punch power in Korean national boxers - Kim, K.-J.; Lee, S.-B.; Park, S. (Exercise Science, 2018)
PURPOSE: The purpose of this study was to investigate the effect of 16-week boxing-specific training on specific fitness and punch power in Korean national team boxers. METHODS: Elite male amateur boxers (n=15) from the Korean national team participated in the study. Weight categories of the participants were light fly, fly, bantam, light, light welter, welter, middle, and light heavy. This boxing-specific training program was designed to improve strength and power, and punching power during pre-season for elite boxers. Boxing-specific training program was composed of three parts; power circuit training, tubing and ball training, and boxing power shuttle-run. The specific fitness such as strength and power and punch power were evaluated before, at the mid-way (8-week), and after the training for all the study participants. RESULTS: As for maximum strength, there were significant improvements in bench press and squat between pre- and post-training. Both the absolute and relative strength of trunk flexion and extension were improved in the post-training compared to the pre-training. Right and left isokinetic power were also improved at the post-training compared to the pre-training. Punch power for facial straight and hook attacks showed significant improvement at the post-training compared to pre-training. Straight punch power was significantly related to the bench press (r=.515, p=.001), and the right arm extension power (r=.535, p=.001). Hook punch power was significantly related to the right arm extension power (r=.417, p=.006). CONCLUSIONS: In conclusion, boxing-specific training was effective to the improvement of strength, power and punch power for elite amateur boxers.